Deborah James. Money from nothing: indebtedness and aspiration in South Africa - Fernandes, Viviane Marinho (Tempo Social, 2017)
Resenha de Deborah James, Money from nothing: indebtedness and aspiration in South Africa. Stanford, Stanford University Press, 2014. 304 pp.